Studi Fenomenologi Transendental untuk Mengupas Makna Pendapatan - Monantun, Widy Pratiwi; Thalib, Mohamad Anwar (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: This research aims to reveal the meaning of income by sharia accounting students. Method: This research falls under the umbrella of the interpretive paradigm. The approach used is phenomenology. There are five data analyses: noema, epoche, noesis, intentional analysis, and eidetic reduction. Results: The research results show that income, which is not limited to results in the form of money. However, there are human values and religiosity inherent in the income obtained. The informants' awareness was formed through Islamic boarding school accounting lectures and accounting theory, which focused on aspects of intellectual intelligence and emotional and spiritual intelligence. Implications: The research results can contribute to curriculum development in the Sharia Accounting study program. Universities can adjust courses or add Sharia accounting learning content not limited to techniques and calculations but includes human values and religiosity. Novelty: results of this study present the meaning of income from the perspective of students majoring in sharia accounting.